2018
DOI: 10.1007/s10658-018-1531-7
|View full text |Cite
|
Sign up to set email alerts
|

Detection of infectious Brome mosaic virus in irrigation ditches and draining strands in Poland

Abstract: Environmental waters, e.g. rivers, lakes and irrigation water, are a good source of many plant viruses. The pathogens can infect plants getting through damaged root hairs or small wounds that appear during plant growth. First results demonstrated common incidence of Tobacco mosaic virus (TMV) and Tomato mosaic virus (ToMV) in water samples collected from irrigation ditches and drainage canals surrounding fields in Southern Greater Poland. Principal objective of this work was to examine if environmental water m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 25 publications
(23 reference statements)
2
21
0
Order By: Relevance
“…Based on published results [2,13] BMV and CfMV can be a new emerging threat for cereal crops. To date CfMV has been detected only in one locations in Poland [11] however, since first detection of BMV in 1999 in Poland, its presence has been reported in different regions of the country [5,8].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on published results [2,13] BMV and CfMV can be a new emerging threat for cereal crops. To date CfMV has been detected only in one locations in Poland [11] however, since first detection of BMV in 1999 in Poland, its presence has been reported in different regions of the country [5,8].…”
Section: Resultsmentioning
confidence: 99%
“…Taking into account the possibility of further spread of the studied pathogens, the designing of specific diagnostic technique as the first step in the successful management of the diseases is needed. Existing diagnostic methods for BMV [2,5,8,[17][18][19] and CfMV [11,[13][14][15][16] have their limitations. ELISA is a time-consuming and laborious technique while conventional RT-PCR assay is able to detect only individual virus species in a single reaction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Infectious tobamovirus particles of TMV and ToMV were found in environmental waters such as ponds and streams. The occurrence of the tobamoviruses was visualized by electron microscopy, and the infectivity of the tobamovirus particles was examined in a biological assay on laboratory test plants [69]. A quantitative and sensitive approach to detect the tobamoviruses in environmental waters was also applied using sensitive reverse-transcription real-time PCR analysis [70].…”
Section: Irrigation Watermentioning
confidence: 99%
“…Another tobamovirus, cucumber green mottle mosaic virus (CGMMV), is also re-emerging and causing significant losses of cucurbit crops ( Dombrovsky et al, 2017 ). Reports of infective tobamoviruses in treated wastewater ( Bačnik et al, 2020 ) or environmental waters ( Jeżewska et al, 2018 ) and their survival in the nutrient solution for up to 6 months ( Pares et al, 1992 ) suggest that water might have an important role in the epidemiology and transmission of these viruses. This has been further confirmed by studies that have reported water-mediated transmission of CGMMV ( Li et al, 2016 ) and other tobamoviruses, and this becomes especially relevant for crops grown using hydroponics ( Mehle and Ravnikar, 2012 ).…”
Section: Introductionmentioning
confidence: 99%